PENGARUH PENGGUNAAN MEDIA BOLA TERHADAP HASIL BELAJAR TENDANGAN MAWASHIGERI PADA KEGIATAN EKSTRAKURIKULER - Asruddin Asruddin; Victor G Simanjuntak; Edi Purnomo (Universitas Tanjungpura, 2020)
Absract : The problem in this study is whether there is the effect of training using assistive media on learning outcomes of Mawashigeri kicks in karate extracurricular students in MTsN Pemangkat, Sambas Regency. The purpose of this study was to determine the effect of training using media aids to the learning outcomes of Mawashigeri kicks in karate extracurricular students. The method used in this study is an experimental research method in the form of Intact-Group Coparison. The research population in this study took all karate extracurricular students towards the learning outcomes of the mawashigeri kick in karate extracurricular students in MTsN Pemangkat, Sambas Regency, totaling 20 students. The sample of this study used a saturated sampling technique of 20 students. Data analysis was performed using t-test analysis (influence test). The results of the study found that the average learning outcomes of Mawashigeri kicks in karate extracurricular students in MTsN Pemangkat District of Sambas experienced a comparison between the groups treated (O1) and those not treated (O2). The results for O1 are an average of 27.4, a minimum score of 25, a maximum score of 30, with a standard deviation of 1.776. Whereas O2 is an average of 22.9, a minimum score of 21, a maximum score of 25, with a standard deviation of 1.370. The results of the ttest = 5.70 is greater than the value of ttable = 2.101, meaning that the hypothesis is accepted, it means that there is an influence of the use of ball media to kick Mawashigeri in karate extracurricular activities in MTsN Pemangkat Sambas Regency. The percentage increase in learning outcomes of karate extracurricular Mawasigeri kicks in MTsN Pemangkat Sambas Regency is 19,65%.Keywords: Ball Media, Mawashigeri Kick Learning Outcomes